Peran Relawan Pajak dalam Memoderasi Pengaruh Pengetahuan dan Kesadaran Perpajakan terhadap Kepatuhan Wajib Pajak - Sindy Amalia; Yulita Zanaria; Elmira Febri Darmayanti (Universitas Muhammadiyah Metro, 2026)
This study aims to analyze the influence of tax knowledge and awareness on individual taxpayer compliance with tax volunteers as a moderating variable. Tax knowledge and awareness are considered as internal factors that influence taxpayer compliance, while tax volunteers act as external factors that are expected to strengthen the relationship. The method used in this study is quantitative with a survey approach through questionnaires distributed to individual taxpayers in the Metro City area. Data were analyzed using the Structural Equation Modeling (SEM) method. The results of the study indicate that tax knowledge and awareness have a significant effect on taxpayer compliance. In addition, tax volunteers have been proven to be able to moderate the influence of tax knowledge and awareness on taxpayer compliance. These findings are expected to contribute to the Directorate General of Taxes in increasing the effectiveness of tax awareness inclusion programs and expanding the role of tax volunteers.